Mass gathering healthcare and safety: current knowledge and future directions - Pigeon, Marc-Antoine; Demers, Anne-Julie; Ciottone, Gregory (Frontiers in Disaster and Emergency Medicine, 2025)
IntroductionMass gathering medicine (MGM) has been a rapidly evolving area of expertise for many years, with pearls and pitfalls emerging from recent literature. Gaps have been identified: lack of a pragmatic definition of MGM, weaknesses in data sets used to report on major events, difficulties with developing tools to help organizers assess health and safety issues. This study aims to map and describe the current body of literature on mass gatherings in order to identify strengths and weaknesses in the healthcare response, guiding future research in the field.MethodsThis study is a bibliometric review. Using the broad research terms “mass gatherings” and “major planned events”, Pubmed, Web of Science and Google Scholar were searched for publications up to Sept. 13, 2024. No restrictions of language or type of articles were used. All gray literature was included. After removal of duplicates, two independent reviewers confirmed relevance, and articles were organized according to date of publication, type of event (7), main subjects categories (11). Further keywords analyses have been conducted using VOSViewer (v.1.6.20).ResultsInitial database searches yielded 4,526 results. After the removal of duplicates and non-related articles, 898 publications remained and have been categorized, dating from 1978 to 2024. Full text analysis was possible for a total of 854 articles. More than 25% of the articles concerned religious events, while categories like infectious diseases and public health were the main subject of more than one third of the papers. Music events, spontaneous gatherings and environmental/remote events were underrepresented. Main topics like heat-related illnesses and environmental health, training and psychosocial aspects were also underrepresented. Keywords analysis allowed for the identification of areas of scarce knowledge that need further development.ConclusionMass gathering health and safety literature has grown rapidly over the past years. This study identified areas of strong knowledge to build upon, while more scarce areas like psychosocial aspects, quality evaluation, management and supervision, training and development of formal expertise are still in need of improvement.